Phytodiversity of Six Regenerating Forest Stands Protected by Joint Forest Management in Koraput Region of Odisha, India - Pathak, Abhay K.; Misra, Malaya K. (Indian Forester, 2015)
The paper reports the results of the analysis of floral composition and similarity index of six recovering dry tropical forest stands, protected by the local community, for 4-, 6-, 8-, 10-, 12- and 20-year periods in the Koraput region of Odisha, India. A minimum of 67 plant species was recorded in 6-year recovering forest stand, while 4-year stand exhibited 72 plant species. Total number of plant species increased from 6- to 20-year stand exhibiting the highest number of 91 species in 20-year stand. The pooled number of all plant species in all the stands was 173 under 151 genera and 57 families. Totalnumber of herbaceous species declined from 34 in 2-year standto 24 in 20-year stand.